An Isolable Phosphaethynolatoborane and Its Reactivity. Issue 8 (25th January 2018) - Wilson, Daniel W. N.; Hinz, Alexander; Goicoechea, Jose M.
Abstract: The synthesis and characterization of a stable phosphaethynolatoborane, [B]OCP (1, [B]=N, N′‐bis(2, 6‐diisopropylphenyl)‐2, 3‐dihydro‐1H‐1, 3, 2‐diazaboryl), is described. The increased triple bond character of the P−C bond in1 relative to the free ion (PCO − ) is probed in a series of reactivity studies. Compound1 readily dimerises in donor solvents to afford a cyclic five‐membered 6π‐aromatic compound, cyclo‐P2 C[B]OCO[B] (2 ), which decarbonylates on UV irradiation. By contrast the nickel‐mediated dimerisation of1 affords the isomeric diphosphacyclobutene [P(CO[B])]2 . When1 is reacted with organolithium reagents such as MesLi (Mes=2, 4, 6‐trimethylphenyl), the boryl moiety shifts and the formation of the lithoxy‐boryl‐phosphaalkene [LiOC[B]P(Mes)]2 was observed. The reactivity of this species towards electrophiles is also described. Abstract : BOCParty : The synthesis, characterization, and reactivity of a stable phosphaethynolatoborane, [B]OCP (1, [B]= N, N ′‐bis(2, 6‐diisopropylphenyl)‐2, 3‐dihydro‐1 H ‐1, 3, 2‐diazaboryl), is described.